2016
DOI: 10.3389/fmicb.2016.00830
|View full text |Cite
|
Sign up to set email alerts
|

On the Kinetic and Allosteric Regulatory Properties of the ADP-Glucose Pyrophosphorylase from Rhodococcus jostii: An Approach to Evaluate Glycogen Metabolism in Oleaginous Bacteria

Abstract: Rhodococcus spp. are oleaginous bacteria that accumulate glycogen during exponential growth. Despite the importance of these microorganisms in biotechnology, little is known about the regulation of carbon and energy storage, mainly the relationship between glycogen and triacylglycerols metabolisms. Herein, we report the molecular cloning and heterologous expression of the gene coding for ADP-glucose pyrophosphorylase (EC 2.7.7.27) of Rhodococcus jostii, strain RHA1. The recombinant enzyme was purified to elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…From these results, it is tempting to speculate that GlcN-6P would represent a signal of high carbon/energy availability in rhodococci, as proposed for other ADP-GlcPPase activators in many bacteria and plants [7,8]. The hypothesis also agrees with hexose-6P (and its amino sugar related) representing a critical metabolic node and itself an allosteric regulator of the activity of actinobacterial ADP-GlcPPase [9,11], particularly in R. jostii [6].…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…From these results, it is tempting to speculate that GlcN-6P would represent a signal of high carbon/energy availability in rhodococci, as proposed for other ADP-GlcPPase activators in many bacteria and plants [7,8]. The hypothesis also agrees with hexose-6P (and its amino sugar related) representing a critical metabolic node and itself an allosteric regulator of the activity of actinobacterial ADP-GlcPPase [9,11], particularly in R. jostii [6].…”
Section: Resultsmentioning
confidence: 60%
“…We previously reported that Rjo ADP-GlcPPase distinctively uses GlcN-1P as a substrate [6]. Although such activity is one order of magnitude lower respect to the use of Glc-1P, it is relevant that for both substrates, Glc-6P exerts a significant allosteric activation of the enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations